Policies and Practices of School Leaderships in Japan: A Case of Leadership Development Strategies in Akita - Yukiko Yamamoto; Naoko Enomoto; Shinobu Yamaguchi (Educational Considerations, 2016)
Reflecting the social and economic change, Japanese education has shifted to decentralization since the 1980s. With an increased autonomy and responsibility, the local government plays an important role to develop competent school leaders. This descriptive study employs case study approach to illustrate current status of leadership development at the local level in Japan. Through the analysis of current policies and practices, it lays out the strategies of leadership development in Akita prefecture. In addition, semi-structured interviews with 17 education leaders were conducted in 2014 and 2015 to explore their perceptions on the leadership development. The study found that the leadership development in Akita is implemented combining formal and informal training activities. While a comprehensive professional development system is implemented strategically, informal learning of competency is commonly exercised. This dual approach enables school leaders to develop their leadership skills and knowledge.
Keywords: Policies; Practices; Leadership; Strategies; Akita; school; leaders; Japan; National Center for Teachers’ Development (NCTD); public schools; Structure; teacher training; opportunities; Two-way channels of communication; Akita Board of Education